A confirmation bias approach to country of ownership cues - Cheah, Isaac; Phau, Ian (Korean Scholars of Marketing Science, 2012)
This paper examines the effect of country of ownership cues, economic nationalistic and consumer ethnocentric tendencies with regards to product judgments and purchase intentions of Australian wines with multi country affiliations. Structural equation modeling supports the model and shows that economic nationalistic bias against foreign affiliations resulted in the Australian consumer’s unwillingness to buy bi-national products.